2016
DOI: 10.1039/c6ce00320f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lithium substitution on the charge compensation, structural and luminescence properties of nanocrystalline Ca10(PO4)6F2activated with Eu3+ions

Abstract: ion co-doped fluorapatite (Ca 10 (PO 4 ) 6 F 2 ) nanocrystals were fabricated using a microwave stimulated hydrothermal technique followed by heat treatment at 500 °C. The concentration of Eu 3+ ions was set to be 1 mol% and that of the Li + ions was in the range of 0.5-5 mol% to investigate the site occupancy preference and charge compensation co-doping. The structural and morphological properties of the obtained samples were determined by using XRD (X-ray powder diffraction) and TEM (transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…By means of the aforementioned expression, the values of Ω 2 and Ω 4 for the Eu 3+ ions were deduced to be 6.9 × 10 −21 cm −2 and 7.6 × 10 −21 cm −2 , respectively. As for the Ω 2 , its value is sharply sensitive to the chemical environment surrounding the dopants, that is, lower symmetry properties of the rare‐earth ions can contribute to the larger Ω 2 value, whereas Ω 4 is only associated with the bulk performance and the rigidity of the host matrixes ,. Evidently, the evaluated Ω 4 value was larger than the Ω 2 value which demonstrated that the Eu 3+ ions could possess the high symmetry sites in the EuF 3 host lattices.…”
Section: Resultsmentioning
confidence: 98%
“…By means of the aforementioned expression, the values of Ω 2 and Ω 4 for the Eu 3+ ions were deduced to be 6.9 × 10 −21 cm −2 and 7.6 × 10 −21 cm −2 , respectively. As for the Ω 2 , its value is sharply sensitive to the chemical environment surrounding the dopants, that is, lower symmetry properties of the rare‐earth ions can contribute to the larger Ω 2 value, whereas Ω 4 is only associated with the bulk performance and the rigidity of the host matrixes ,. Evidently, the evaluated Ω 4 value was larger than the Ω 2 value which demonstrated that the Eu 3+ ions could possess the high symmetry sites in the EuF 3 host lattices.…”
Section: Resultsmentioning
confidence: 98%
“…Because of this, only samples in the 0.5 -3 mol% concentration range and in the 500 -1000°C temperature range were characterized via the PL emission and excitation spectra, as shown in Figures 8, 9 and 10. The representative excitation/emission spectra recorded at 618 nm emission line corresponding to the maximum intensity of the The positions of maxima of f-f transitions are independent on the host lattice structure and remains almost constant due to a good isolation of the f shells by the external orbitals as well as low electron-lattice coupling 19,26 . The room-temperature emission spectra of the Ca (10-3x) Eu 2x (PO 4 ) 6 F 2 nanopowders were acquired in the spectral range from 17 500 nm to 14 000 cm -1 under pulsed 266 nm excitation as a function of optically active ions concentrations (2x = 0.5 -3 mol%) for three calcination temperatures (600°, 800°, 1000°C) and as a function of annealing temperature (as-prepared -1000°C).…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The dopant ions can be substituted at both calcium sites depending on size and charge compensation ,. As far as optical properties of the rare earth dope fluorapatites matrixes in concerned, reports on doped with rare earth ions such as Pr 3+ , Nd 3+ , Tm 3+ ,Eu 3+ , Yb 3+ /Ho 3+ , Er 3+ /Yb 3+[37] are available, where studies were mostly concerned as phosphors materials and laser hosts. However to the best our knowledge reports on Sm 3+ based fluorapatites is not reported yet.…”
Section: Introductionmentioning
confidence: 99%